Radiotherapy plus pembrolizumab for advanced urothelial carcinoma: results from the ARON-2 real-world study - Rizzo, Mimma; Soares, Andrey; Grande, Enrique; Bamias, Aristotelis; Kopp, Ray Manneh; Lenci, Edoardo; Buttner, Thomas; Salah, Samer; Grillone, Francesco; de Carvalho, Icaro Thiago; Tapia, Jose Carlos; Gucciardino, Calogero; et al. (Scientific reports, 2024)
The addition of metastasis-directed radiotherapy (MDRT) to immunotherapy in patients with advanced urothelial carcinoma (aUC) has shown promising results. We report the real-world data from the ARON-2 study (NCT05290038) on the impact of conventional (CRT) or stereotactic body radiotherapy (SBRT) on the outcome of aUC patients receiving pembrolizumab after platinum-based-chemotherapy. Medical records of 837 patients were reviewed from 60 institutions in 20 countries. Two hundred and sixty-two patients (31%) received radiotherapy (cohort A), of whom 193 (23%) received CRT and 69 (8%) received SBRT. Patients were assessed for overall survival (OS), progression-free survival (PFS), and overall response rate (ORR). Univariate and multivariate analyses were used to explore the association of variables of interest with OS and PFS. With a median follow-up of 22.7 months, the median OS was 10.2 months, 6.8 months and 16.0 months in no RT, CRT and SBRT subgroups (p = 0.005), with an 1y-OS rates of 47%, 34% and 61%, respectively (p < 0.001). The 1y-OS rate in the SBRT subgroup were significantly higher for both lower (63%) and upper tract UC (68%), for pure urothelial histology (63%) and variant histologies (58%), and for patients with bone (40%) and lymph-node metastases (61%). Median PFS was 4.8 months, 9.6 months and 5.8 months in the CRT, SBRT and no RT subgroups, respectively (p = 0.060). The 1y-PFS rate was significantly higher (48%) in the SBRT population and was confirmed in all patient subsets. The difference in terms of ORR was in favour of SBRT. Our real-world analysis showed that the use of SBRT/pembrolizumab combination may play a role in a subset of aUC patients to increase disease control and possibly overall survival.
Keywords: kombinovaná terapie; Humans; Antineoplastic Agents, Immunological; lidé středního věku; Pembrolizumab; karcinom z přechodných buněk; Urothelial carcinoma; urologické nádory; Female; Aged; dospělí; výsledek terapie; senioři; lidé; humanizované monoklonální protilátky; doba přežití bez progrese choroby; Stereotactic radiation therapy; Urologic Neoplasms; radiochirurgie; Radiation therapy; Adult; Radiosurgery; Antibodies, Monoclonal, Humanized; ženské pohlaví; ARON-2 study; Male; nádory močového měchýře; Middle Aged; Retrospective Studies; Treatment Outcome; Carcinoma, Transitional Cell; Aged, 80 and over; senioři nad 80 let; protinádorové látky imunologicky aktivní; retrospektivní studie; Progression-Free Survival; Combined Modality Therapy; mužské pohlaví; Urinary Bladder Neoplasms; Real-world data